Améliorer la santé et le bien-être des Madelinots anglophones : Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2018)
La stratégie décrite dans le présent document est conçue comme une proposition à discuter avec les membres de la collectivité et les autres intervenants, et qui peut être adaptée et précisée au besoin. Elle est fondée sur une documentation pertinente en la matière et sur une évaluation des besoins réaliseee avec la contribution des acteurs locaux. Cette stratégie fait partie d'un processus de développement communautaire en continu, lequel a permis de réaliser un portrait de la communauté, des consultations publiques et un certain nombre d'actions qui s'inscrivent dans le cadre de la vision pour "Une communauté dynamique et en santé, sans drogues, sans alcool, ni violence, assurant un environnement favorable pour tous les membres de la communauté."
Keywords: Official Language Minority Community (OLMC)

Improving the Health and Well-Being of English-Speaking Magdalen Islanders : A Strategy for the Healthy Development of Youth - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Magdalen Islanders (CAMI), 2018)
The strategy outlined in this document is meant as a draft to be discussed with community members and other stakeholders, and to be adapted and refined as seen fit. It is based on current relevant literature, and a needs assessment carried out with input from local stakeholders. This strategy is part of an on-going community development process, which has included a community profile, community consultations, and a number of actions being carried out in the pursuit of the vision for “A dynamic, healthy community, free of drugs, alcohol and violence, with a supportive environment for all community members.”
Keywords: Official Language Minority Community (OLMC)

An Adapted Approach to Supporting English-Speaking Children (0-5) and Families in the Province of Quebec - Community Health and Social Services Network (CHSSN) (2018)
The primary objective of this document is to further encourage and inspire English-speaking communities to collaborate with stakeholders in their regions offering programs and services to children and families. The document may also serve as a useful tool for stakeholders to become more aware of specific needs often faced by Englishspeaking children and their families and learn about some of the adapted approaches and initiatives underway.

Building Confidence : Conversing with the English Community : A How-to Toolkit - Community Health and Social Services Network (CHSSN) (2018)

Key Demographic and Socio-economic Characteristics of Quebec's English-speaking Youth (15-29) - Community Health and Social Services Network (CHSSN) (2018)
This CHSSN report profiles the situation of English-speaking citizens of Quebec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood. Youth is a stage of life characterized by challenges that can be decisive in the quality of life of individuals and their communities and for the vast majority of Quebecers aged 15-29, these milestones are completing school, gaining occupational experience and even starting a family and establishing a household. This report offers current information organized to support “the village” - from policy-makers and program managers through to public institutions and community organizations and networks - whose actions impact the lives of minority language youth striving to build their future and the future of all Quebec’s citizens.
Keywords: Official Language Minority Community (OLMC)